Selective recovery of cobalt from the cathode materials of NMC type Li-ion battery by ultrasound-assisted acid leaching and microemulsion extraction. Issue 16 (1st November 2020) - Wang, Wen-Yu; Yen, Clive H.; Hsu, Jeng-Kai
ABSTRACT: A selective recovery process for cobalt from the cathode materials of Li-ion batteries is demonstrated in this report. First, acid leaching was applied to dissolve the metals from the lithium-metal oxides. It was found out that with the assistance of probe type ultrasonication, manganese could be simultaneously separated by precipitation. This phenomenon would reduce the difficulty for later separation. Next, water-in-oil microemulsion extraction was applied for direct extraction of cobalt from the other metals. The cobalt extraction yield was 98% and purity was 96%. Moreover, the microemulsion system could be reused for 100 times without losing its extraction ability.